THE DISEASE OF MORTALITY IN HESIOD'S THEOGONY: PROMETHEUS, HERAKLES, AND THE INVENTION OF KLEOS. (6th May 2016) - Mueller, Melissa
Abstract : Hesiod's Theogony is not overtly concerned with the world of mortals. The place of humans in the Theogony nevertheless holds a certain fascination, perhaps more for what is not revealed—our origins, for example—than for what is. Focusing on a relatively neglected passage of the poem ( Theogony 521-32), I want to trace here the way Hesiod lays out the cosmic coordinates of kleos ('fame' or 'glory') with a view to better situating the condition of mortality within the poem as a whole. Kleos, as we will see, is part of the fallout for humans of the battle of wits between Zeus and Prometheus: it is the compensation for their new, temporally inflected existence.